Too Much to Choose: How Product Overload in Retail Leads to Consumer Decision Fatigue? - Ramli S; Dahri, Nur Wahyunianti; Aqil, Muhammad; Nurfaidah (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
The sample used consisted of 300 respondents, selected using purposive sampling techniques. The present study employed a covariance-based structural equation modeling (CB-SEM) approach to analyze the data collected from respondents. The findings indicated that the marketing mix and consumer behavior exert a substantial influence on purchasing decisions, while brand image demonstrated an absence of significant impact. Furthermore, the marketing mix does not exert a substantial influence on customer satisfaction. Consumer behavior and brand image are found to have a significant impact on customer satisfaction. The marketing mix and consumer behavior, which serve as mediators in purchasing decisions, have been demonstrated to exert a significant influence on customer satisfaction. Conversely, brand image, which functions as a mediator in purchasing decisions, has been found to have an insignificant influence on customer satisfaction.